2021
DOI: 10.1007/s41999-021-00531-2
|View full text |Cite
|
Sign up to set email alerts
|

Nursing homes during the COVID-19 pandemic: a scoping review of challenges and responses

Abstract: Introduction COVID-19 has caused unprecedented challenges in nursing homes. In this scoping review, we aimed to describe factors that contributed to the spread and mortality of COVID-19 in nursing homes and provide an overview of responses that were implemented to try to overcome such challenges. Methods The MeSH terms “Nursing homes” and “COVID-19” were searched in MEDLINE Ovid, and English language articles were retrieved that were published between 1 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 105 publications
2
94
1
1
Order By: Relevance
“…However, there are marked differences in the spread and mortality figures between countries. The factors behind the variations between NHs include resident-related factors, facility and staffing characteristics [ 3 , 5 , 6 ]. It has been suggested that high-quality NHs have lower prevalence of COVID-19 cases than those with lower quality although confounding factors may underlie this [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are marked differences in the spread and mortality figures between countries. The factors behind the variations between NHs include resident-related factors, facility and staffing characteristics [ 3 , 5 , 6 ]. It has been suggested that high-quality NHs have lower prevalence of COVID-19 cases than those with lower quality although confounding factors may underlie this [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the impact of the COVID-19 pandemic on long-term residential care and the well-documented preference of individuals to remain living at home, enhancing community-based care services is an emergent priority. 2 , 3 In 2021, an estimated 23.9 million hours of government-funded home support services (termed domiciliary care in some regions) were delivered to over 55,000 people aged 65 years and older in Ireland. 4 State-funded home support encompasses assistance with activities of daily living (ADLs), most commonly personal care 5 and is allocated based on a needs assessment, and is currently not income assessed in Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention should be paid to patients returning from high-incidence regions, those who have been in contact with infected people and those recovering from a COVID-19 infection, in case of prolonged viral shedding and asymptomatic infections. Rigorous screening and testing concepts should also be implemented for patients coming from nursing homes, as virus transmission from asymptomatic patients has previously been linked to outbreaks (Byambasuren et al 2020;Borras-Bermejo et al 2020;Giri et al 2021). Whenever possible, the number of people present at in-person appointments should be kept to a minimum and additional nursing personnel should only accompany patients if absolutely necessary.…”
Section: Risk Of Exposure Is Increased By In-person Appointmentsmentioning
confidence: 99%